Spot survei entomologi di Desa Binawara, Kabupaten Tanah Bumbu pasca pemberian obat pencegahan massal filariasis - Abdullah Fadilly; Wulan Sari Rasna Giri Sembiring; Besral Besral; Akmad Rosanji; M Rasyid Ridha; Budi Hairani (JHECDs: Journal of Health Epidemiology and Communicable Diseases, 2019)
Filariasis in South Kalimantan is still a problem, especially in rural areas, this is possible because there are still many potential places for vector breeding such as rice fields, forests and swamps. In Tanah Bumbu District, filariasis cases were reported as many as 38 cases where as many as 35 cases were found in Batulicin and Kusan Hilir Sub-districts, while as many as 3 recent cases in 2015 in Angsana District. The purpose of this study was to determine various types of mosquitoes, density, age, and habitat characteristics of potential mosquitoes as filariasis vectors in Binawara Village, Tanah Bumbu District. The study was carried out with descriptive observasional design and cross sectional approach in May 2018. Entomological surveys conducted included habitat surveys, mosquito capture by human bait, and surgery. The results showed the dominance of the habitat found was swamp. There were 12 species of mosquitoes caught i. e. Ma. uniformis, Ma. dives, Ma. bone, An. barbirostris, An. maculatus, Ae. linnetaopenis, Ae. albopictus, Ae. aegypti, Cx. sitiens,, Cx. crasipes, Cx. quinquefasciatus, and Cq. crassipes. The density of mosquitoes sucks the highest blood, Ma. dives, with a value of 4 mosquitoes / person / hour (MHD) and 3 mosquitoes / person / night (MBR). The results of surgery are high parity for Ma.dives, Ma.uniformis and Cx. quinquefasciatus shows that the mosquito has undergone a gonothrophic cycle with a relative age of mosquitoes that have the opportunity to be filariasis vectors. Longevity of mosquito age that should be suspected as filariasis vectors are 42.43 days for Ma.uniformis and 47.96 days for Cx. quinquefasciatus. Although filariasis transmission has not been proven in this study, but with the discovery of potential vectors and the discovery of positive patients, the awareness of filariasis transmission needs to be increased. In terms of increasing vector control of PHBS and self protection from mosquito bites (repellent and the use of closed clothing) can be a form of control in order to avoid filariasis transmission.